TRAVEL CORRIDOR TECHNIQUE OF WILD TURKEY MANAGEMENT - G. A. Gehrken (Wildlife Society Bulletin)
Abstract Travel corridors provided the eastern wild turkey (Meleagris gallopavo silvestris) easy access to suitable habitats at Union Camp Corporation's Palmetto Bluff Plantation in southeastern South Carolina. Even‐aged short rotation pine management was practiced on 65 percent of the forest, and produced 414,769 cubic meters (m3) of pine and 62,525 m3 of hardwood. Turkey management was practiced on 35 percent of the forest land, and a sizeable turkey population maintained.